Study on digital twins in network lifecycle management - Da WANG; Tao SUN; Xiaowen SUN; Jianchao GUO; Jie SUN; Guo CHEN; Aidong YANG; Ye OUYANG (Dianxin kexue)
As consumers’ demands for mobile services have become more abundant and diversified, the architecture and functions of mobile network have become more complex.With the development of 5G technology, 5G mobile network could realize on-demand orchestration and flexible exposure of network capabilities, which made higher requirements for network lifecycle management.Digital twins technology could be used to assist the network lifecycle management, so as to improve the network management quality, reduce network risks and costs, and achieve the visual perception and the real-time closed-loop control.The network digital twin platform and application cases show that the proposed network digital twins platform can realize visual monitoring and analysis of mobile network operation key performance indicators and quickly diagnosis of network faults.